Analisis Yuridis Terhadap Tindak Pidana Narkotika Ditinjau dari Pendekatan Rehabilitatif dan Represif dalam Prespektif Hukum - Ginting, Enus; Rahmayanti, Rahmayanti; Ismaidar, Ismaidar (Blantika: Multidisciplinary Journal, 2025)
Narcotics crimes are a form of crime that has a serious impact on individuals, society, and even the sustainability of the state. The problem of narcotics is not only seen as a criminal act, but also as a health, social, and humanitarian problem. Therefore, the countermeasures require a comprehensive legal approach, both rehabilitative and repressive. The rehabilitative approach emphasizes recovery efforts for narcotics abusers as victims, so that they can return to function socially in society. Meanwhile, the repressive approach is focused on strict law enforcement against perpetrators of illicit narcotics trafficking that undermine the legal order and national security. From a legal perspective, the regulation of narcotics in Indonesia is regulated in Law Number 35 of 2009 concerning Narcotics, which contains these two dimensions. Based on this, this study formulates two main problems: (1) how the criminal law regulation of narcotics crimes is reviewed from a rehabilitative and repressive approach from a legal perspective, and (2) how the urgency of the application of the law to narcotics crimes is reviewed from these two approaches. This research aims to find out and comprehensively analyze the effectiveness of narcotics criminal law regulation by emphasizing the balance between legal certainty, utility, and justice. Thus, the legal urgency in dealing with narcotics crimes lies in the need for a proper, humane, and effective criminal policy. This dual approach is expected to create a legal system that not only reduces the number of narcotics crimes, but also provides long-term solutions through victim recovery and community protection.